Safety and tolerability of adjunctive brivaracetam as intravenous infusion or bolus in patients with epilepsy. (25th May 2016) - Klein, Pavel; Biton, Victor; Dilley, Deanne; Barnes, Matthew; Schiemann, Jimmy; Lu, Sarah
Summary: Objectives: An intravenous (IV) formulation of brivaracetam (BRV), a selective, high‐affinity ligand for synaptic vesicle protein 2A, has been developed. We investigated the safety, tolerability, and pharmacokinetics of adjunctive IV BRV administered as a bolus or infusion to adults with epilepsy. Methods: A phase III, multicenter, randomized, four‐arm, parallel‐group study (NCT01405508) of patients aged 16–70 years with focal or generalized epilepsy uncontrolled by 1–2 antiepileptic drugs was undertaken. The study comprised a 7‐day baseline period, a 7‐day double‐blind run‐in period (oral BRV 200 mg/day or placebo [PBO] twice daily [BID]), and 4.5‐day open‐label evaluation period (IV BRV 200 mg/day BID; 2‐min bolus or 15‐min infusion, total nine doses). Patients were randomized 1:1:1:1 PBO/BRV bolus; PBO/BRV infusion; BRV/BRV bolus; BRV/BRV infusion. Safety and tolerability were assessed using adverse events, electrocardiography, vital signs, and laboratory assessments. BRV plasma concentrations were measured before and 15 min after the first and last IV doses. Results: Of the 105 patients randomized (53.3% women; 77.1% white; mean [standard deviation; SD] age 41.6 [12.2] years), 103 (98.1%) completed the study. Treatment‐emergent adverse event (TEAE) incidence during IV BRV was similar whether IV BRV was initiated first (70.6%) or followed oral BRV (66.0%), and whether it was administered as a bolus (71.2%) or infusion (65.4%). Injection‐related TEAEs were reported by 9.6% of patients following bolus and 11.5% following infusion. No serious TEAEs were reported. IV BRV plasma concentrations were higher after the first dose in the conversion groups than initiation groups, and slightly higher in the bolus arm than the infusion arm; concentrations were similar in all patients after the last IV dose. Significance: IV BRV was generally well tolerated, with similar tolerability as a bolus or infusion and independent of de novo administration or as conversion from oral BRV tablets. IV BRV may be an option for patients who are unable to receive oral BRV.